Self-Fashioning in Ona Pleirytė-Puidienė’s Diary - Avižinienė, Birutė (Literatūra, 2025)
This article examines Ona Pleirytė-Puidienė’s diary Mano gyvenimo knyga (The Book of My Life, 1905–1929) through the lens of self-fashioning. Drawing on Stephen Greenblatt’s concept of self-fashioning, the theoretical perspective is further refined by engaging feminist literary criticism that has renewed approaches to diary studies. The research is informed by the works of Jennifer Sinor and Rebecca Steinitz, who focus on the specific practice of diary writing and the questions it raises. In Pleirytė-Puidienė’s diary, the figure of the idealist Vaidilutė (Pagan Priestess), a fictional persona created by the author, embodies a dual structure of identity: public “masks” worn for society and the private, authentic self revealed in solitude. Vaidilutė represents the dominant femininity norm of the time – a morally superior woman who chooses self-sacrifice for others. This identity, most strongly articulated in the first and second parts of the diary, is complicated by unrecorded yet evident aspects of self-perception, such as gender identity, illness, and addiction, particularly in the third part. Self-fashioning in Pleirytė-Puidienė’s diary demonstrates that the diary, traditionally regarded as a private form of writing, is shaped not only by individual self-construction but also by the cultural norms of its time.